Development of Improved Mountage Using Mango Plant Twigs During Lack of Sufficient Number or Absence of Mountages on Field for Silkworm Cocoon - C.J. Hiware2; S.B. Avhad2, S.T. Naphade1*, (Recent Research in Science and Technology, 2010)
In the present investigation the mango tree twigs were used as mountages along with the plastic mountages to study their efficacy. After feeding on mulberry leaves for several days, silkworms of the 5th instar stop feeding and begin to spin cocoon. To spin cocoons, ripe, mature silkworms need mountages (cocoon frames) as supports. The process of mooving mature larva on to the cocoons frame is called mounting. Mounting process in silkworm rearing is the most labour intensive operation to be simplified. Mounting and mountages considerably influence the quality and quantity of cocoons. This low cost readily available, emergency Mango tree twig mountages are helping farmers when there is lack of sufficient number or absence of mountages on field. Thus such kind of mountages play important role in economic yield of silkworm cocoon and to save the cocoon crop. This study shows effect on post-cocoon parameter and it is positive as compare to plastic mountages. The mango plant twigs, mountages are easily available on field and cheaper to use by saving the labour cost. Keywords: Mountages, Mango plant, Silkworm cocoon, Plastic mountage